1979
DOI: 10.1093/ajcp/72.6.984
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assurance of Gram-stained Direct Smears

Abstract: Clinical laboratories do not always prepare and examine direct smears. In part, this may be explained by lack of control over the precision and accuracy of the procedure, which has diminished confidence in direct smears among both laboratory scientists and clinicians. Objective criteria were established for enumeration of cells and placement of bacteria in identification categories. Two methods for monitoring the accuracy and reproducibility of their application were studied: (1) examination of previously exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…In 1979, Bartlett et al described a program for staining and evaluation of replicate smears for purposes of monitoring the interpretive skills of medical technologists (39). In 1980, Bartlett and Rutz described a detailed cost analysis of the effect of applying control to the assessment of the quality and extent of work performed on specimens of lower respiratory tract secretions, wound exudate, cervicovaginal exudate, and urine (37).…”
Section: Advent Of Government Regulationmentioning
confidence: 99%
“…In 1979, Bartlett et al described a program for staining and evaluation of replicate smears for purposes of monitoring the interpretive skills of medical technologists (39). In 1980, Bartlett and Rutz described a detailed cost analysis of the effect of applying control to the assessment of the quality and extent of work performed on specimens of lower respiratory tract secretions, wound exudate, cervicovaginal exudate, and urine (37).…”
Section: Advent Of Government Regulationmentioning
confidence: 99%
“…This contamination can be quantified by evaluating Gram-stained sputum samples for polymorphonuclear leukocytes and squamous epithelial cells. The resulting objective measure, called the quality (Q) score, has been validated and recommended for use in evaluating the quality of the specimen (1).…”
mentioning
confidence: 99%
“…In order to determine smear adequacy and increase the specificity of the methods of microbiological investigation, the samples were examined under optical microscopy by the method described by Bartlett et al for grading the quality of sputum. (19) The sputum samples selected for microscopy were examined by Gram staining and smeared onto media for the culture of aerobic bacteria. This was achieve by a semiquantitative technique, samples from each patient being cultured on a blood agar plate, a chocolate agar plate, and a MacConkey agar plate.…”
Section: Resultsmentioning
confidence: 99%
“…Despite being low, the blood culture positivity rate found in the present study is similar to those reported in other studies (5-14%). (10,27) Despite being performed after the use of the qualitative test described by Bartlett et al (19) and having their positivity assessed only in the properly collected samples, neither sputum of CAP cases began to be standardized in the hospital under study. Regarding elucidation of the diagnosis, loss to clinical follow-up after hospital discharge made it impossible to arrive at a definitive etiological diagnosis in some cases (those in which a second biological sample for serology was not collected).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation